The role of 'accompagnement' in the end-of-life debate in France: from solidarity to autonomy. - Gaille, M; Horn, R (Springer, 2016)
This article traces the way autonomy has become a recognised value in health care in France. In a country that based its social fundamentals on the very idea of solidarity for many years, autonomy has long been considered a foreign 'Anglo-American principle'. Taking the example of the end-of-life debate, the article shows, however, how the use of the French term 'accompagnement' allowed autonomy to be redefined and to be associated with the concept of solidarity. Exploring the arguments used over the past 25 years in professional guidelines, parliamentary reports, ethics committee reports, and legal texts, the authors describe the shift that took place in public and legal discourses on end-of-life care. The analysis demonstrates how the scope of autonomy has been limited by other social values, such as the protection of the dying person, in order to become an accepted social value in its own right. The example of the French end-of-life debate shows that depending on how the concept of autonomy is adapted and applied in a specific context, it can be compatible with the idea of solidarity. Such compatibility has been challenged previously in the international bioethics debate. By demonstrating the possibility of combining autonomy and solidarity, this article makes an important contribution to the international bioethics debate and to the dialogue between countries that are often perceived as significantly different.